2010
DOI: 10.1097/qai.0b013e3181b843f0
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Reasons for and Outcomes of Patients Lost to Follow-Up in Antiretroviral Therapy Programs in Africa Through a Sampling-Based Approach

Abstract: Objectives Losses to follow-up after initiation of antiretroviral therapy (ART) are common in Africa and are a considerable obstacle to understanding the effectiveness of nascent treatment programs. We sought to characterize, through a sampling-based approach, reasons for and outcomes of patients who become lost to follow-up. Design Cohort study. Methods We searched for and interviewed a representative sample of lost patients or close informants in the community to determine reasons for and outcomes among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

26
235
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 254 publications
(274 citation statements)
references
References 19 publications
26
235
5
Order By: Relevance
“…This forces mothers to resort to walking long distances. This finding is in agreement with other studies, where distance to the clinic and transport cost were found to be major barriers to retention in care in a wide variety of settings in Africa including Uganda [12].…”
Section: Discussionsupporting
confidence: 93%
“…This forces mothers to resort to walking long distances. This finding is in agreement with other studies, where distance to the clinic and transport cost were found to be major barriers to retention in care in a wide variety of settings in Africa including Uganda [12].…”
Section: Discussionsupporting
confidence: 93%
“…The study found that the relative risk of death was associated with lower CD4 cell counts and HIV depression scores, which was also found in other studies (Cornell, Myer, Kaplan, Bekker & Wood, 2009;Geng et al, 2009;Hartzell et al, 2008). This finding suggests that treating depression at ART initiation as previously recommended (Jia et al, 2005) may be indicated in this South African population.…”
Section: Discussionsupporting
confidence: 78%
“…[6,9] To our knowledge, there is no other literature examining early attendance rates at an integrated neuropsychiatric clinic in SA following inpatient initiation of ART. Integrated care has been shown to improve outcomes, with a number of different models of mental health and HIV integrated programmes described in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…[8] Reasons why patients may fail to attend clinic appointments include patient choice, forgetfulness, acute illness, hospitalisation, transfer to another treatment site and death. [9] Research has shown an association between clinic attendance and adherence to medication. [10] Integrated HIV and mental healthcare might result in improved rates of clinic attendance, by providing personalised follow-up, specifically tailored to the needs of those with a mental illness as well as HIV infection.…”
Section: Articlementioning
confidence: 99%